Adaptive proportional derivative controller using fuzzy logic. (2016) - Maity, Ritu Rani De; Mudi, Rajani K.
Design of an improved fuzzy rule-based auto-tuning PD controller has been done with conventional Ziegler-Nichols PID controller. It has been observed that for the very common system in industry, the integrating system, the classical Ziegler-Nichols tuned PID controller (ZNPID) gives excessively large value of overshoot and settling time. Here, the proposed controller is a fuzzy auto-tuning PD (FAPD) controller. The value of the derivative gain of the conventional PD controller is continuously updated by a factor α. The value of α is determined depending on the process trend, i.e., normalised value of error (e) and change of error (Δe) and 49 or nine fuzzy if then rules. In FAPD, the updating factor 'α' continuously updates the value of derivative gain to provide an overall good performance during set point change and load disturbance. To study the effectiveness of the proposed controller FAPD has been tested and compared with other PID controllers for different integrating systems with varying dead time.